Cyclohexane Vibronic States: A Combined VUV Spectroscopy and Theoretical Study - Edvaldo Bandeira; Alessandra S. Barbosa; Nykola C. Jones; Søren V. Hoffmann; Márcio H. F. Bettega; Paulo Limão-Vieira (Molecules)
In this work, we provide results from a joint experimental and theoretical study of the vibronic features of cyclohexane (C6H12) in the photon energy range of 6.8–10.8 eV (182–115 nm). The high-resolution vacuum ultraviolet (VUV) photoabsorption measurements, together with quantum chemical calculations at the time-dependent density functional theory (TDDFT) level, have helped to assign the major electronic excitations to mixed valence–Rydberg and Rydberg transitions. The C6H12 photoabsorption spectrum shows fine structure which has been assigned to CH2 scissoring, <semantics><msubsup>v3′</msubsup><mfenced>a1g</mfenced></semantics>, CH2 rocking, <semantics><msubsup>v4′</msubsup><mfenced>a1g</mfenced></semantics>, C–C stretching, <semantics><msubsup>v5′</msubsup><mfenced>a1g</mfenced></semantics>, and CCC bending/CC torsion, <semantics><msubsup>v24′</msubsup><mfenced>eg</mfenced>,</semantics> modes. Molecular structure calculations at the DFT level for the neutral and cationic electronic ground-states have shown the relevant structural changes that are operative in the higher-lying electronic states. Photolysis lifetimes in the Earth’s atmosphere are shown to be irrelevant, while the main atmospheric sink mechanism is the reaction with the •OH radical. Potential energy curves have been obtained at the TDDFT level of theory, showing the relevance of interchange character mainly involving the CH2 scissoring, <semantics><msubsup>v3′</msubsup><mfenced>a1g</mfenced>,</semantics> and CH2 rocking, <semantics><msubsup>v4′</msubsup><mfenced>a1g</mfenced>,</semantics> modes, while Jahn–Teller distortion yields weak vibronic coupling involving the non-totally symmetric CCC bending/CC torsion, <semantics><msubsup>v24′</msubsup><mfenced>eg</mfenced>,</semantics> mode.